2011
DOI: 10.3892/ol.2011.311
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of surgical stress of laparoscopically assisted vaginal radical hysterectomy and lymphadenectomy and laparotomy for early-stage cervical cancer

Abstract: Abstract. The aim of this study was to objectively evaluate the benefits of laparoscopically assisted vaginal radical hysterectomy and lymphadenectomy for early-stage cervical cancer. Clinical data were prospectively collected from patients with IA-IIB cervical cancer who underwent laparoscopically assisted vaginal radical hysterectomy (n1=33) and laparotomy (n2=30). Peripheral blood samples were obtained prior to surgery and at 1 and 2 h into the operation, as well as on days 1, 4 and 7 following surgery to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 34 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…Most published studies on LARVH are retrospective on surgical and pathological data and only a few authors reported the survival outcomes and recurrence rates after LARVH [2,[23][24][25]. Like our study, Zhang et al [26] compared LARVH with TARH in 77 women with early cervical cancer that confirmed no difference in recurrence rate (9.4% in LARVH and 33.3% in TARH), length of disease free survival (DFS) (46.4 months in LARVH and 45.4 months in TARH), OS rate (93.8% in LARVH and 86.7% in TARH) between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Most published studies on LARVH are retrospective on surgical and pathological data and only a few authors reported the survival outcomes and recurrence rates after LARVH [2,[23][24][25]. Like our study, Zhang et al [26] compared LARVH with TARH in 77 women with early cervical cancer that confirmed no difference in recurrence rate (9.4% in LARVH and 33.3% in TARH), length of disease free survival (DFS) (46.4 months in LARVH and 45.4 months in TARH), OS rate (93.8% in LARVH and 86.7% in TARH) between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…[17,18] Many studies have shown that LARVH is associated with less intra- and postoperative complications universally. [711,1316] However, in China no one reported the long-term prognosis of LARVH maybe because of new technique without long time follow up. In our study, we reported the survival outcomes based on long-term follow up which was scarce data.…”
Section: Discussionmentioning
confidence: 99%
“…The technical feasibility of laparoscopically assisted radical vaginal hysterectomy (LARVH) as treatment for early-stage cervical cancer has been well established through a series of institution, [716] which suggest that LARVH may have an intraoperative reduction in blood loss, transfusion requirement, and hospital stay but longer operative time. But just a few authors [8,12,13,15] reported the survival outcomes which was most important question to evaluate the prognosis of therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Postoperative immune dysfunction is a problem for patients undergoing surgery for malignant tumors, as it affects the rate of infectious complications, clinical outcomes and the growth of disseminated tumor cells (4)(5)(6). Particularly in the elderly with cancer, improved postoperative immunity may result in more favorable long-term oncological results (7,8). Therefore, it is critically important to improve the surgery-induced immune suppression and restore the immune function following surgery in patients with cancer.…”
Section: Introductionmentioning
confidence: 99%